2014
DOI: 10.1001/jama.2014.12854
|View full text |Cite
|
Sign up to set email alerts
|

Serological Responses to an Avian Influenza A/H7N9 Vaccine Mixed at the Point-of-Use With MF59 Adjuvant

Abstract: for the DMID 13-0032 H7N9 Vaccine Study Group IMPORTANCE Human infections with avian influenza A/H7N9 have resulted in high morbidity and mortality in China.OBJECTIVE To compare safety and immunogenicity of different doses of influenza A/Shanghai/2/13 (H7N9) vaccine mixed with or without the MF59 adjuvant. DESIGN, SETTING, AND PARTICIPANTS Multicenter, randomized, double-blind, phase 2 trial at 4 US sites enrolled 700 adults aged 19 to 64 years beginning in September 2013; 6-month follow-up was completed in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 42 publications
(2 reference statements)
8
83
2
2
Order By: Relevance
“…Our study revealed that methylation frequency of APC is markedly increased in primary tumors, which was consistent with previous reports in rectal (Leong et al, 2011), breast (Mulligan et al, 2014), colorectal, and gastrointestinal cancers (Esteller et al, 2001). Furthermore, APC displayed higher degrees of methylation in patients with lymph node metastasis or higher TNM stages, which was also in accordance with results from breast cancer studies (Mulligan et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed that methylation frequency of APC is markedly increased in primary tumors, which was consistent with previous reports in rectal (Leong et al, 2011), breast (Mulligan et al, 2014), colorectal, and gastrointestinal cancers (Esteller et al, 2001). Furthermore, APC displayed higher degrees of methylation in patients with lymph node metastasis or higher TNM stages, which was also in accordance with results from breast cancer studies (Mulligan et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Subsequent infection or immunization with a variant strain would likely be an effective route to generate broadly reactive anti-H5 antibodies. Such strategies are known to be effective within influenza subtypes (25,48,49). Our structural understanding of H5.3 supports the hypothesis that repeated challenge through immunization or infection is an effective strategy to enhance universal binding determinants, such as a CDRH3 loop that effectively binds conserved features of the RBS, similar to the natural receptor, while minimizing strainspecific interactions.…”
Section: Resultssupporting
confidence: 68%
“…nanoparticle | vaccine platform | replicon | viruses | parasites T oday, there are a range of vaccine technologies used clinically, with varied use of inactivated pathogens, molecular antigens, adjuvants, delivery technologies, administration routes, and dosing regimes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although existing vaccine systems have had a huge impact on prevention of infectious disease, challenges remain.…”
mentioning
confidence: 99%